Characterizing stomatal attributes and photosynthetic induction in relation to biochemical changes in Coriandrum sativum L. by foliar-applied zinc oxide nanoparticles under drought conditions - Ahmed, Shakil; Khan, Muhammad Tajammal; Abbasi, Asim; Haq, Inzamam Ul; Hina, Aiman; Mohiuddin, Muhammad; Tariq, Muhammad Atiq Ur Rehman; Afzal, Muhammad Zaheer; Zaman, Qamar uz; Ng, Anne Wai Man; Li, Yong (Frontiers in Plant Science, 2023)
Abiotic stress particularly drought will remain an alarming challenge for sustainable agriculture. New approaches have been opted such as nanotechnology to reduce the negative impact of drought stress and lessen the usage of synthetic fertilizers and pesticides that is an inevitable problem these days. The application Zinc oxide nanoparticles (ZnO NPs) has been recognized an effective strategy to enhance the plant growth and crop production during abiotic stress. The aim of current study was to investigate the role of ZnO NPs in drought stress management of drought susceptible Coriandrum sativum (Coriander) in two consecutive seasons. Drought regimes (Moderate Drought Regime;MDR and Intensive Drought Regime (IDR)were developed based on replenishment method with respect to 50% field capacity (FC) of full irrigated (FI; control) plants. Results showed that foliar application of 100-ppm ZnO NPs improve the net photosynthesis (Pn), stomatal conductance (C) and transpiration rate (E) and boost up the photosynthetic capacity associated with photosynthetic active radiation (PAR) in MDR. Similarly, 48% to 30% improvement of chlorophyll b (Chlb) content was observed in MDR and one-fold to 41% in IDR during both seasons in ZnO NPs supplemented plants. The amount of ABA in leaves showed a decreasing trend in MDR and IDR in 1st season (40% and 30%) and (49% and 33%) in 2nd season compared to untreated ZnO NPs plants. ZnO NPs treated plants showed an increment in total soluble sugars (TSS), total phenolics content (TPC), and Total flavonoids content (TFC) in both drought regimes. Whereas, abaxial surface showed high stomatal density (SD) and stomatal index (SI) than adaxial surface in foliar supplied NPs plants. Further, ZnO NPs improve the magnitude of stomata ultrastructures like stomatal length (SL), stomatal width (SW) and pore length (PL) for better adaptation against drought. PCA analysis revealed efficacy of ZnO NPs induced drought tolerance in mild and intensive stress regimes. These results suggest that 100 ppm ZnO NPs can be used to ameliorate drought tolerance in C. sativum plants.